The Effect of Laparoscopic Radical Hysterectomy Surgical Volume on Oncology Outcomes in Early-Stage Cervical Cancer - Li, Pengfei; Liu, Jiaqi; Wang, Li; Kang, Shang; Yang, Ying; Guo, Jianxin; Yao, Jilong; Lu, Anwei; Wang, Zhonghai; Lin, Bin; Li, Zhiqiang; Bin, Xiaonong; et al. (Frontiers in Surgery, 2021)
Purpose: To examine the association between surgical volume and surgical and oncological outcomes of women with stage IB1 cervical cancer who underwent laparoscopic radical hysterectomy (LRH). Methods: We retrospectively analyzed the oncological outcomes of 1,137 patients with stage IB1 cervical cancer receiving LRH from 2004 to 2016. The surgical volume for each surgeon was defined as low [fewer than 50 surgeries, n = 392(34.5%)], mid [51-100 surgeries, n = 315(27.7%)], and high [100 surgeries or more, n = 430(37.8%)]. Surgical volume-specific survival was examined with Kaplan–Meier analysis, multivariable analysis, and propensity score matching. Results: The operative times of the high-volume group (227.35 ± 7.796 min) were significantly shorter than that of the low- (272.77 ± 4.887 min, p < 0.001) and mid-volume (255.86 ± 4.981 min, p < 0.001) groups. Blood loss in the high-volume group (169.42 ± 8.714 ml) was significantly less than that in the low-volume group (219.24 ± 11.299 ml, p = 0.003). The 5-year disease-free survival (DFS) and overall survival (OS) in the low-volume, mid-volume, and high-volume groups were similar (DFS: 91.9, 86.7, and 89.2%, p = 0.102; OS: 96.4, 93.5, and 94.2%, p = 0.192). Multivariable analysis revealed surgical volume was not an independent risk factor for OS or DFS. The rate of intraoperative and postoperative complications was similar among the three groups (p = 0.210). Conclusions: Surgical volume of LRH may not be a prognostic factor for patients with stage IB1 cervical cancer. Surgery at high-volume surgeon is associated with decreased operative time and blood loss.